2020
DOI: 10.1093/ehjqcco/qcz066
|View full text |Cite
|
Sign up to set email alerts
|

Association between heart failure and perioperative outcomes in patients undergoing non-cardiac surgery

Abstract: Aims Heart failure (HF) affects ∼5.7 million US adults and many of these patients develop non-cardiac disease that requires surgery. The aim of this study was to determine perioperative outcomes associated with HF in a large cohort of patients undergoing in-hospital non-cardiac surgery. Methods and results Adults ≥18 years old undergoing non-cardiac surgery between 2012 and 2014 were identified using the Healthcare Cost and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…A study conducted in Sweden showed that the crude and adjusted HRs for 30day mortality after elective surgery in patients with CHF were 5.36 and 1.79, respectively (9). An analysis of 21,560,996 surgical hospitalisations revealed that the adjusted OR for in-hospital perioperative mortality in patients was 2.15 (11). Another study found similar results; compared with patients without CHF, patients with CHF had a 96% increased risk of 30-day mortality (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Sweden showed that the crude and adjusted HRs for 30day mortality after elective surgery in patients with CHF were 5.36 and 1.79, respectively (9). An analysis of 21,560,996 surgical hospitalisations revealed that the adjusted OR for in-hospital perioperative mortality in patients was 2.15 (11). Another study found similar results; compared with patients without CHF, patients with CHF had a 96% increased risk of 30-day mortality (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although CHF has been recognised as a risk factor for postoperative mortality and has been incorporated into several risk indicators (4)(5)(6)(7)(8), few studies have examined the relationship between CHF and postoperative mortality. The hazard ratio (HR)/odds ratio (OR) produced by previous studies on the relationship between CHF and the prognosis of surgical patients varied widely (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…This study evaluated the intersection of etiology, comorbidities, and undergoing ERCP. It is well-documented that conditions like CHF, CLD, anemia, coagulopathies, and DM can negatively affect surgical outcomes in general [6][7][8][9][10][11], and in the case of CLD, previous negative outcomes have been directly linked to ERCP [5]. While most studies only look at mortality in reference to outcomes, this study also evaluated non-medical outcomes, such as total charges and patient length of stay (LOS).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HF in the VA Surgical Quality Affairs population was 7.9% in patients undergoing non-cardiac surgery and preexisting HF resulted in increased mortality with an odd's ratio of 1.69 (CI 1.57–1.76) ( 39 ). Patients with preexisting HF undergoing non-cardiac surgery in other very large retrospective cohort studies (AHRQ-NIS) with less selected patient populations likewise carried dramatically increased mortality and rehospitalization risks ( 40 ). Preexisting HF causes rehospitalization due to CV and non-CV causes in more than 10% of the patients compared to 2.5% ( 41 ).…”
Section: Relevance Of Heart Failurementioning
confidence: 99%
“…In addition, surgery induces an adrenergic stress response originating from pain and tissue destruction and translating into hemodynamic changes such as increased blood pressure and heart rate. Augmented adrenergic responses will trigger more inflammation and increased blood pressure and heart rate increase the risk for deterioration of LV function ( 40 , 42 , 45 ).…”
Section: Relevance Of Heart Failurementioning
confidence: 99%